Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the equation of a circle given its center and radius, we use the standard formula for the equation of a circle:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
Where:
- [tex]\((h, k)\)[/tex] is the center of the circle
- [tex]\(r\)[/tex] is the radius of the circle
For this specific problem:
- The center of the circle is [tex]\((-3.2, 2.1)\)[/tex], thus [tex]\(h = -3.2\)[/tex] and [tex]\(k = 2.1\)[/tex].
- The radius [tex]\(r\)[/tex] is [tex]\(4.3\)[/tex].
Substituting these values into the standard formula, we get:
[tex]\[ (x - (-3.2))^2 + (y - 2.1)^2 = (4.3)^2 \][/tex]
Simplifying the equation, notice that subtracting a negative number is the same as adding the positive:
[tex]\[ (x + 3.2)^2 + (y - 2.1)^2 = (4.3)^2 \][/tex]
Now, let's compare this derived equation with the given options:
A. [tex]\((x + 2.1)^2 + (y - 3.2)^2 = 4.3^2\)[/tex]
B. [tex]\((x - 2.1)^2 - (y + 3.2)^2 = (4.3)^2\)[/tex]
C. [tex]\((x - 3.2)^2 + (y + 2.1)^2 = (4.3)^2\)[/tex]
D. [tex]\((x + 3.2)^2 + (y - 2.1)^2 = 4.3^2\)[/tex]
Clearly, the correct equation matches option D:
[tex]\[ (x + 3.2)^2 + (y - 2.1)^2 = 4.3^2 \][/tex]
Therefore, the equation of the circle is:
[tex]\[ \boxed{(x + 3.2)^2 + (y - 2.1)^2 = 4.3^2} \][/tex]
The correct answer is option D.
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
Where:
- [tex]\((h, k)\)[/tex] is the center of the circle
- [tex]\(r\)[/tex] is the radius of the circle
For this specific problem:
- The center of the circle is [tex]\((-3.2, 2.1)\)[/tex], thus [tex]\(h = -3.2\)[/tex] and [tex]\(k = 2.1\)[/tex].
- The radius [tex]\(r\)[/tex] is [tex]\(4.3\)[/tex].
Substituting these values into the standard formula, we get:
[tex]\[ (x - (-3.2))^2 + (y - 2.1)^2 = (4.3)^2 \][/tex]
Simplifying the equation, notice that subtracting a negative number is the same as adding the positive:
[tex]\[ (x + 3.2)^2 + (y - 2.1)^2 = (4.3)^2 \][/tex]
Now, let's compare this derived equation with the given options:
A. [tex]\((x + 2.1)^2 + (y - 3.2)^2 = 4.3^2\)[/tex]
B. [tex]\((x - 2.1)^2 - (y + 3.2)^2 = (4.3)^2\)[/tex]
C. [tex]\((x - 3.2)^2 + (y + 2.1)^2 = (4.3)^2\)[/tex]
D. [tex]\((x + 3.2)^2 + (y - 2.1)^2 = 4.3^2\)[/tex]
Clearly, the correct equation matches option D:
[tex]\[ (x + 3.2)^2 + (y - 2.1)^2 = 4.3^2 \][/tex]
Therefore, the equation of the circle is:
[tex]\[ \boxed{(x + 3.2)^2 + (y - 2.1)^2 = 4.3^2} \][/tex]
The correct answer is option D.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.